Growth, Fitness, and Overwinter Survival of a Shattercane (Sorghum bicolor ssp. drummondii)×Grain Sorghum (Sorghum bicolor ssp. bicolor) F2 Population. Issue 5 (23rd July 2018) - Schmidt, Jared J.; Yerka, Melinda K.; Pedersen, Jeffrey F.; Lindquist, John L.
Abstract: Although sorghum [ Sorghum bicolor (L.) Moench ssp. bicolor ] is the fifth most important grain crop in terms of global production, no commercial hybrids carry genetically engineered (GE) traits for resistance to insect pests or herbicides due to regulatory concerns about gene flow to weedy relatives. However, non-GE herbicide resistance currently is being developed in grain sorghum and will likely transfer to related weeds. Monitoring the impact of this new nuclear technology on the evolution and invasiveness of related weeds requires a baseline understanding of the population biology of grain sorghum genes once they transfer to in situ weed populations. We previously characterized the rate of gene flow from grain sorghum to shattercane [ Sorghum bicolor (L.) Moench nothosubsp. drummondii (Steud.) de Wet ex. Davidse], a conspecific weed relatively common in North America; as well as the ecological fitness of an F1 population when S. bicolor nothosubsp. drummondii was the maternal parent. Here we report the ecological fitness of a S. bicolor nothosubsp. drummondii × S. bicolor ssp. bicolor F2 population relative to its crop and weed parents. Parental and F2 populations were grown in two Nebraska environments in 2012 and 2013. Traits evaluated included overwinter survival, field emergence, biomass production and partitioning at anthesis, total seed production, and 100-seed weight. Results indicated that F2 traits were generally intermediate between the parents, but more similar to S. bicolor nothosubsp. drummondii than to grain sorghum. The one exception was overwinter survival, which was nearly 0% for both the F2 and the grain sorghum parent in these northern environments. Thus, the frequency of crop alleles stably introgressed into S. bicolor nothosubsp. drummondii populations appears to primarily depend on overwinter survival of the F2 and which selective pressures are imposed upon it by the cropping system. These data provide needed baseline information about the environmental fate of nuclear genetic technologies deployed in this important global crop.